2013
DOI: 10.1590/s0074-0276108042013003
|View full text |Cite
|
Sign up to set email alerts
|

Induction of protective T-helper 1 immune responses against Echinococcus granulosus in mice by a multi-T-cell epitope antigen based on five proteins

Abstract: In this study, we designed an experiment to predict a potential immunodominant T-cell epitope and evaluate the protectivity of this antigen in immunised mice. The T-cell epitopes of the candidate proteins (EgGST, EgA31, Eg95, EgTrp and P14-3-3) were detected using available web-based databases. The synthesised DNA was subcloned into the pET41a+ vector and expressed in Escherichia coli as a fusion to glutathione-S-transferase protein (GST). The resulting chimeric protein was then purified by affinity chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The recombinant vaccine was developed from the G1 genotype of E. granulosus , and protectivity against other genotypes is unclear . The use of chimeric protein constructs of different epitopes may constitute a different approach .…”
Section: Immune Response In the Intermediate Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant vaccine was developed from the G1 genotype of E. granulosus , and protectivity against other genotypes is unclear . The use of chimeric protein constructs of different epitopes may constitute a different approach .…”
Section: Immune Response In the Intermediate Hostmentioning
confidence: 99%
“…It is generally proposed by the literature that a Th2 response would favour parasite establishment as opposite to a parasite‐killing Th1 response. However, the picture appears much more complex, as (i) often a mixed Th1/Th2 response is present in infected hosts, (ii) regulatory mechanisms are likely to control both Th1 and Th2 parasite‐killing effector mechanisms (for example, Tregs have been recently described locally increased as early as 5 days post‐PSC injection ), and (iii) it is often difficult to say whether a particular type of immune response is the cause or the result of a certain infection status . Some evidence supports an increased parasite‐killing effect when Th1 type responses are boosted.…”
Section: Immune Response In the Intermediate Hostmentioning
confidence: 99%
“…2 The proliferation of specific B-cell lymphocytes from mice immunized with Emy162; ***P < 0.001 Fig. 3 The ELISA test of the B-cell antigen peptide of Emy162 acting with serum of AE patients; ***P < 0.001 polypeptide vaccine [21], and others, have been developed in recent years. Zheng et al [22] suggested that prenyltransferase, together with prenylcysteine oxidase, might act as a novel drug to target hydatidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some research demonstrated the potential for successful transfer of immunity against E. granulosus to lambs via colostrum; this study showed that exposed ewes to three oral infections with E. granulosus eggs, as well as immunized ewes with E. granulosus oncospheral antigens, transferred a remarkable level of immunity to lambs through colostrum. However, the natural immunity is often concomitant with some degrees of injury to the internal organs including liver, lung, heart, and spleen as well as economics detriments [ 26 ].…”
Section: Discussionmentioning
confidence: 99%